2020
DOI: 10.1038/s41540-020-00142-w
|View full text |Cite
|
Sign up to set email alerts
|

Linking metabolic phenotypes to pathogenic traits among “Candidatus Liberibacter asiaticus” and its hosts

Abstract: Candidatus Liberibacter asiaticus (CLas) has been associated with Huanglongbing, a lethal vector-borne disease affecting citrus crops worldwide. While comparative genomics has provided preliminary insights into the metabolic capabilities of this uncultured microorganism, a comprehensive functional characterization is currently lacking. Here, we reconstructed and manually curated genome-scale metabolic models for the six CLas strains A4, FL17, gxpsy, Ishi-1, psy62, and YCPsy, in addition to a model of the close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…Few studies have reported the in planta genome‐wide transcriptome profiling of CLas, until a recent study that employed RNA sequencing for analyses of CLas expression profile by using phloem‐enriched samples from CLas‐infected citrus trees (Zuñiga et al ., 2020). However, less than 0.53% of total reads were identified as CLas reads in RNA‐Seq data derived from CLas‐infected citrus phloem samples (Zuñiga et al ., 2020). The use of CLas‐enriched dodder RNA sample in this study provided a higher resolution of CLas transcripts, and we observed similar gene expression patterns of CLas both in citrus host and dodders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported the in planta genome‐wide transcriptome profiling of CLas, until a recent study that employed RNA sequencing for analyses of CLas expression profile by using phloem‐enriched samples from CLas‐infected citrus trees (Zuñiga et al ., 2020). However, less than 0.53% of total reads were identified as CLas reads in RNA‐Seq data derived from CLas‐infected citrus phloem samples (Zuñiga et al ., 2020). The use of CLas‐enriched dodder RNA sample in this study provided a higher resolution of CLas transcripts, and we observed similar gene expression patterns of CLas both in citrus host and dodders.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have been reported CLas transcriptome profiling by using RNA‐Seq, mainly due to low abundance of CLas RNA compared with host RNA. A recent study analysed in citrus and psyllids CLas expression profiles using RNA‐Seq, but the analysis lacked enough depth because CLas reads were minoritary (Zuñiga et al, 2020). Therefore, to gain insight into CLas–host interaction during infection, higher resolution of in planta CLas transcripts is required.…”
Section: Introductionmentioning
confidence: 99%
“…This value falls in the range observed by other authors, such as the mapping of 0.50% of transcriptome reads of the whole body of B. cockerelli against the Lso genome ( Ibanez et al, 2014 ). Transcriptome analysis of Las was comparatively carried out in citrus and in dodder, with read mapping ranging from 0.11% to 1.44%, respectively ( Li et al, 2021 ), while in adventitious citrus roots in culture media and in alimentary canals of D. citri , 0.28% to 2.51% of reads mapped to Las genome ( Zuñiga et al, 2020 ). In contrast, only 0.01% of reads obtained from infected grapevine mapped against the flavescence dorée phytoplasma ( Abbà et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only 0.01% of reads obtained from infected grapevine mapped against the flavescence dorée phytoplasma ( Abbà et al, 2014 ). Las DNA detection in relation to host DNA is higher in psyllids than in citrus ( Selvaraj et al, 2018 ), and this favors the obtention of Las nucleic acid from psyllids for metagenomic ( Duan et al, 2009 ; Lin et al, 2013 ) and metatranscriptomic ( Zuñiga et al, 2020 ) analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation